Geminate and Nongeminate Pathways for Triplet Exciton Formation in Organic Solar Cells. Issue 16 (16th March 2022) - Privitera, Alberto; Grüne, Jeannine; Karki, Akchheta; Myers, William K.; Dyakonov, Vladimir; Nguyen, Thuc‐Quyen; Riede, Moritz K.; Friend, Richard H.; Sperlich, Andreas; Gillett, Alexander J.
Abstract: Organic solar cells (OSCs) have recently shown a rapid improvement in their performance, bringing power conversion efficiencies to above 18%. However, the open‐circuit voltage of OSCs remains low relative to their optical gap and this currently limits efficiency. Recombination to spin‐triplet excitons is a key contributing factor, and is widely, but not universally, observed in donor–acceptor blends using both fullerene and nonfullerenes as electron acceptors. Here, an experimental framework that combines time‐resolved optical and magnetic resonance spectroscopies to detect triplet excitons and identify their formation mechanisms, is reported. The methodology is applied to two well‐studied polymer:fullerene systems, PM6:PC60 BM and PTB7‐Th:PC60 BM. In contrast to the more efficient nonfullerene acceptor systems that show only triplet states formed via nongeminate recombination, the fullerene systems also show significant triplet formation via geminate processes. This requires that geminate electron–hole pairs be trapped long enough to allow intersystem crossing. It is proposed that this is a general feature of fullerene acceptor systems, where isolated fullerenes are known to intercalate within the alkyl sidechains of the donor polymers. Thus, the study demonstrates that engineering good donor and acceptor domain purity is key for suppressing losses via triplet excitons in OSCs. Abstract : Recombination to triplet excitons is a key contributing factor to the large nonradiative voltage losses in organic solar cells. An experimental framework combining time‐resolved optical and magnetic resonance spectroscopies that can detect triplet excitons and identify their formation mechanism is reported. This allows for clear differentiation between geminate and nongeminate pathways and provides design rules for the suppression of triplet losses.